Usos hegemônicos e não hegemônicos do território no sudeste do Pará: a moderna mineração e o circuito inferior da economia urbana em Parauapebas - Reis, Walison Silva (2016)
This study describes and analyzes the process of modernization of the Southeastern part of Pará since the early 1950's due to geopolitical guidelines of the State towards the integration of the Amazon's territory to the national and international economy by exploiting the potential of its natural resources. The municipality of Parauapebas, emancipated from Marabá at the end of the 1980s, emerged as a concrete result of economistic strategies of the state, through the relations of power established with the extraction and export of iron ore, led by former state company CVRD - now called Vale SA. - Parauapebas has combined the contradictions of modern activities of mining policy, focused on foreign trade, and small non - modern activities, thinly capitalized and poorly organized, rooted to the local life of the city and/or region, thereby constituting an antagonistic space. Thus, the purpose of this research is to drill down and understand the urban dynamics of Parauapebas from the perspective of the Theory of Two Circuits of Urban Economics, formulated by Santos (2008), that segments the urban areas of developing countries into Upper and Lower Circuits.Small commercial activities and services, analyzed in neighborhoods New Town and Rio Verde, allowed for a delineation on the inconsistencies, as well as a comprehension of the expressions of the lower urban economy circuit, brought forth by the excluded population of modern mining industry, which is indifferent to the local reality, and confined in terms of manpower.